Cause and mechanism of the Seti River flood, 5th May 2012, western Nepal (Journal of Nepal Geological Society, 2013)
A catastrophic flash flood has occurred in the Seti River in the morning of May 5, 2012. An attempt has been made to find out the cause of the flood which originated form very remote inaccessible area lying in the Western slope of the Annapurna IV peak. Comparative Analysis of the Landsat ETM satellite images of 20th April, 2012 and 6th May, 2012 revealed that the area of about 32000 square meter of the southern ridge 1.5 kilometer away from the Annapurna IV peak failed in the north western direction. The impact of descending mass of the failed mountain from 6850 meters to 4500 meters almost vertically pulverized the ice, sediment and rock. The impact even triggered seismicity at 9:09.56 AM, local time which was recorded all over the 21 stations of National Seismological Centre. The closest seismic station at Dansing which is 32 km. south west from the area recorded the high signals for 70 minutes which corresponds to the duration of the debris flow. Lab analysis of the flood water sample revealed the density of the flow as 1.88 gm/cc. Analysis of the satellite based hourly rainfall GSMaP NRT from the period form 20th April-6th May 2012 revealed that there were just 4 occurrences of rainfall which amounted less than I mm/hour in the source area of the avalanche. The rainfall > 6mm/hour which occurred in the Kharapani area on 4 May was localized rainfall which did not extend to the avalanche area. Lack of systematic disaster preparedness caused huge loss of life and property even though the early warning message was received from the Ultralight pilot who was flying close to the area. The avalanche triggered high intensity floods which have similar characteristics to glacier lake outburst floods (GLOFs) have emerged as a new hazard in the Himalaya.